Professores iniciantes egressos do curso de Pedagogia e o abandono da carreira docente no município de Rondonópolis/MT - Silva, Adriane Pereira da (2018)
The current study is linked to the Graduate Program in Education of the Federal University of Mato Grosso, university campus of Rondonópolis (PPGEdu/UFMT/CUR) and has its origin in the project of the Observatory of Education (OBEDUC/CAPES/INEP/SECADI), entitled “Graduates of Licentiate in Pedagogy and the challenges of the practice in narratives: the university and the school in an interdisciplinary process of insertion of the beginner teacher in the teaching career”, which investigates the beginner teacher, the professional development and difficulties, as well as the educational training needs. The research addressed the beginner teacher and the abandonment of the teaching career, theme which is little referred to in Brazilian researches. It is considered that the beginner teacher is a professional with up to five years of teaching and that abandonment are the cases in which the teacher is inducted by civil service exam, however, afterwards requests resignation. For the development of the investigation the qualitative approach was adopted, utilizing as procedure and instrument of data collection the document analysis in Official Gazette, of the state and the city, as well as data from the sector of Human Resources in the Municipal Secretary of Education in Rondonópolis/MT and from the schools of the state network, as well as narrative interviews and searches on electronic sites. The questions that guided the investigation were: What perceptions do the beginner teachers resigned from teaching manifest about the education received and what expectations do they make regarding the teaching profession? What disenchantments do they present in assuming the teaching profession? What led them to the abandonment? The subjects of the research are six female teachers that accepted to be part of the investigation, being three from the municipal network and three from the state network, inducted by civil service exam, and later resigned by their own request. The results point out that the reasons related to the requests of resignation, in other words, the abandonment of teaching is intrinsically associated to the excess of the obligations that are charged to the teachers when taking office of the civil service and moreover, to the distance between the professional education and the reality encountered in the schools.